Problematika Tukar Guling Tanpa Ikrar Wakaf (Studi Kasus Tanah Wakaf di Semarang) - Achmad Noor Ardhy; Agus Sarono (Notarius, 2023)
AbstractThe exchange of bolsters is carried out by Nadzir in order to keep the managed waqf assets productive and provide benefits to the community. One of the conditions that must be met for the registration of waqf property is the Waqf Pledge Deed while the Nurul Ikhlas Mosque obtains waqf without being accompanied by a waqf pledge before a notary. Problems arise when the heirs of the replacement land will take care of the certificate of ownership. This article is a case study in which data collection was obtained through interviews and observations, it was found that to obtain a waqf pledge deed which is a condition for managing a swap deed, the replacement land heirs must obtain a statement letter of relinquishment of the waqf property rights from the wakif heirs. The length of management time and the number of related parties who have died make the swapping process longer and more complicated.Keyword: waqf; waqf pledge deedAbstrakTukar guling dilakukan nadzir demi menjaga harta benda wakaf yang dikelola tetap produktif dan memberi manfaat bagi masyarakat. Salah satu syarat yang harus dipenuhi untuk pendaftaran harta benda wakaf adalah Akta Ikrar Wakaf sementara Masjid Nurul Ikhlas memperoleh wakaf tanpa disertai ikrar wakaf dihadapan notaris. Permasalahan muncul ketika ahli waris dari tanah pengganti akan mengurus sertipikat hak milik. Artikel ini merupakan suatu studi kasus yang pengumpulan datanya diperoleh melalui wawancara serta observasi, diperoleh bahwa untuk mendapatkan akta ikrar wakaf yang menjadi syarat mengurus akta tukar guling, maka ahli waris tanah pengganti harus mendapat surat pernyataan pelepasan hak atas harta benda wakaf dari ahli waris wakif. Lamanya waktu pengurusan serta banyaknya pihak terkait yang telah meninggal menjadikan proses tukar guling menjadi lebih lama dan rumit.Kata kunci: wakaf; akta ikrar wakaf